Application of Data Mining Technology in Book Information Management. Issue 2 (May 2021) - Dong, Kun
Abstract: With the development of big data mining technology, it plays a very important role in the university library management system. It effectively solves the problem of data searching in traditional library management. This article mainly analyzes and studies the application of data mining technology in libraries.